Identifikasi Ulasan Wisatawan Daring untuk Meningkatkan Layanan Destinasi Wisata - Ni Wayan Anggreni; I Made Artayasa; I Wayan Sukita (LEMBAGA PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT AKADEMI PARIWISATA DENPASAR, 2025)
Tourism is a strategic sector in Indonesia's national development with significant contributions to the economy and cultural image of the nation. However, the quality of tourist destination services remains a major challenge, especially in facing the dynamics of digital tourist behavior that increasingly relies on online reviews as the main reference. This study aims to explore tourist perceptions of services and sustainability of tourist destinations in Indonesia through content analysis of digital reviews on Google Reviews. The approach used is descriptive qualitative with thematic analysis methods of domestic and foreign tourist reviews published between March and May 2025. The study focused on three leading destinations: Borobudur Temple, Nusa Penida, and Komodo National Park. The results of the study show that service aspects such as natural beauty and historical value are highly appreciated, while ticket prices, infrastructure, and waste management are often criticized. There are striking differences in perception between domestic and foreign tourists, especially regarding expectations of comfort, cultural values, and service standards. In addition, tourist reviews also express concern for sustainability issues, including environmental preservation and conservation ethics. The conclusion of this study emphasizes the importance of utilizing online reviews as strategic data for decision-making in managing more inclusive, adaptive, and sustainable tourist destinations